Rapid prototyping of robotic systems - Smuda, William James. (Monterey, California, 2012)
This effort describes a systems engineering approach to the design and implementation of software for prototyping robotic systems. Developing networked robotic systems of diverse physical assets is a continuing challenge to developers. Problems often multiply when adding new hardware/software artifacts or when reconfiguring existing systems. This work describes a method to create model-based, graphical domain-specific languages. Domain-specific languages use terms understandable to domain engineers as well as abstract software engineering decisions. This methodology enables domain engineers to create quality executable prototypes without being versed in the intricacies of software engineering.